Monodisperse Magnetic Nanoparticles for Theranostic Applications - Ho, Don; Sun, Xiaolian; Sun, Shouheng (Accounts of chemical research, 2011)
Effective medical care requires the concurrent monitoring of medical treatment. The combination of imaging and therapeutics allows a large degree of control over the treatment efficacy and is now commonly referred to as “theranostics”. Magnetic nanoparticles (NPs) provide a unique nanoplatform for theranostic applications because of their biocompatibility, their responses to the external magnetic field, and their sizes which are comparable to that of functional biomolecules. Recent studies of magnetic NPs for both imaging and therapeutic applications have led to greater control over size, surface functionalization, magnetic properties, and specific binding capabilities of the NPs. The combination of the deep tissue penetration of the magnetic field and the ability of magnetic NPs to enhance magnetic resonance imaging sensitivity and magnetic heating efficiency makes magnetic NPs promising candidates for successful future theranostics. In this Account, we review recent advances in the synthesis of magnetic NPs for biomedical applications such as magnetic resonance imaging (MRI) and magnetic fluid hyperthermia (MFH). Our focus is on iron oxide (Fe3O4) NPs, gold-iron oxide (Au–Fe3O4) NPs, metallic iron (Fe) NPs, and Fe-based alloy NPs, such as iron-cobalt (FeCo) and iron-platinum (FePt) NPs. Because of the ease of fabrication and their approved clinical usage, Fe3O4 NPs with controlled sizes and surface chemistry have been studied extensively for MRI and MFH applications. Porous hollow Fe3O4 NPs are expected to have similar magnetic, chemical, and biological properties as the solid Fe3O4 NPs, and their structures offer the additional opportunity to store and release drugs at a target. The Au–Fe3O4 NPs combine both magnetically active Fe3O4 and optically active Au within one nanostructure and are a promising NP platform for multimodal imaging and therapeutics. Metallic Fe and FeCo NPs offer the opportunity for probes with even higher magnetizations. However, metallic NPs are normally very reactive and are subject to fast oxidation in biological solutions. Once they are coated with a layer of polycrystalline Fe3O4 or a graphitic shell, these metallic NPs are more stable and provide better contrast for MRI and more effective heating for MFH. FePt NPs are chemically more stable than Fe and FeCo NPs and have shown great potential as contrast agents for both MRI and X-ray computed tomography (CT) and as robust probes for controlled heating in MFH.